2011
DOI: 10.1007/s10532-011-9523-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the bioremoval of Cr(VI) and TOC in biofilters under continuous operation using response surface methodology

Abstract: In the present study, the bioremoval of Cr(VI) and the removal of total organic carbon (TOC) were achieved with a system composed by an anaerobic filter and a submerged biofilter with intermittent aeration using a mixed culture of microorganisms originating from contaminated sludge. In the aforementioned biofilters, the concentrations of chromium, carbon, and nitrogen were optimized according to response surface methodology. The initial concentration of Cr(VI) was 137.35 mg l(-1), and a bioremoval of 85.23% wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
1
2
0
1
Order By: Relevance
“…2C also shows a similar effect of yeast extract on the % Cr(VI) removal during the interaction of molasses and yeast extract. These results are similar to the results obtained for the interaction of carbon, nitrogen sources, and Cr(VI) concentration on Cr(VI) removal reported by Leles et al [16]. According to that report, the variation in reduction capacity decreased with increasing Cr(VI) concentration [16].…”
Section: Response Surface Plotssupporting
confidence: 91%
See 1 more Smart Citation
“…2C also shows a similar effect of yeast extract on the % Cr(VI) removal during the interaction of molasses and yeast extract. These results are similar to the results obtained for the interaction of carbon, nitrogen sources, and Cr(VI) concentration on Cr(VI) removal reported by Leles et al [16]. According to that report, the variation in reduction capacity decreased with increasing Cr(VI) concentration [16].…”
Section: Response Surface Plotssupporting
confidence: 91%
“…The increase in reduction capacity with glucose and molasses was probably due to an increase in metabolic activity. It has been found that chromium transport into the bacterial cell depends on energy; therefore, it is glucose dependent [16].…”
Section: Effects Of Carbon Sourcesmentioning
confidence: 99%
“…Em pesquisas desenvolvidas na Faculdade de Engenharia Química da Universidade Federal de Uberlândia, utilizando meios sintéticos simulando um efluente de curtume, foi utilizada aplicação de campo magnético em micro-organismos de culturas mistas para redução de Cr(VI) a Cr(III) (Dalcin et al, 2011, Leles et al, 2012, Moura, 2012.…”
Section: Introductionunclassified
“…Studies have shown that certain bacterial species are capable of transforming hexavalent chromium (VI) into a valence with less toxicity, such as chromium (III) . The processes by which the microorganisms interact with toxic metals to allow for their removal or recovery include the following: bioaccumulation, biosorption, and enzymatic reduction .…”
Section: Introductionmentioning
confidence: 99%